Blood lead levels of maternal-cord pairs, children and adults who live in a central urban area in Turkey - Kirel, Birgül; Akşit, M Arif; Bulut, Hakan (The Turkish Journal of Pediatrics, 2005)
Lead levels were measured in blood samples of 99 adults, 180 children and 143 pregnant women living in Eskişehir, an urban area in Turkey. One hundred and twenty 120 cord blood and 93 breast-milk samples were also obtained. Mean lead level in blood of adults, children, pregnants, cord blood and in breast-milk samples were 3.13 +/- 1.4 microg/dl, 3.56 +/- 1.7 microg/dl, 2.8 +/- 1.5 microg/dl, 1.65 +/- 1.4 microg/dl and 2.34 +/- 1 microg/L, respectively. It was higher in men than in women in adults (p